Differences in family planning outcomes between military and general populations in Kinshasa, Democratic Republic of the Congo: a cross-sectional analysis. Issue 12 (22nd December 2018) - Akilimali, Pierre; Anglewicz, Philip; Engale, Henri Nzuka; Kurhenga, Gilbert Kabanda; Hernandez, Julie; Kayembe, Patrick; Bertrand, Jane
Abstract : Objectives: To examine family planning outcomes among women living in military camps in Kinshasa, Democratic Republic of the Congo, and compare these outcomes with a representative sample of non-military women in Kinshasa. Participants: Women of reproductive ages, 15–49 years. We compare two populations: women living in military camps and the general (non-military) population in Kinshasa. Study design: For sampling, we used a two-stage cluster sampling design, where we first randomly selected enumeration areas (EA), and then randomly selected women within each EA (separately for each of the two populations). We administered a survey on contraceptive use and family planning to all participating women. We use bivariate and multivariate analysis to compare these populations for a range of family planning outcomes. Results: We find many statistically significant differences between women in military camps and general female population of Kinshasa. Although they do not have more children, women in military camps are less likely to be using contraception (all methods OR 0.24, 95% CI 0.11 to 0.53; modern methods OR 0.25, 95% CI 0.08 to 0.79; traditional methods OR 0.41, 95% CI 0.24 to 0.71) and less knowledgeable about many family planning methods (less likely to have heard of implants (OR 0.23, 95% CI 0.11 to 0.48), injectables (OR 0.19, 95% CI 0.08 to 0.44), condoms (OR 0.23, 95% CI 0.12 to 0.47), withdrawal (OR 0.05, 95% CI 0.02 to 0.17) and rhythm (OR 0.12, 95% CI 0.03 to 0.44) methods), while at the same time they are more likely to want to limit their births (OR 5.17, 95% CI 2.52 to 10.62), and less likely to have obtained their preferred family planning method (OR 0.14, 95% CI 0.03 to 0.64). Conclusions: Women in military camps in Kinshasa appear to be an important and underserved population with regard to family planning. Our results suggest that women in military camps have limited access to modern family planning methods.